The Society and the Community: Equivalence and Difference - Žukauskaitė, Audronė (Sociologija. Mintis ir veiksmas, 1999)
The aim of the article is to discuss the notion of community in the contemporary French philosophy. The author takes her departure from a notion of a community that is defined negatively - by distinguishing it from society that is built according to the logic of identity or equivalence. The author notes that such a notion is inseperable from the notion of society and is aimed to point out the difference of and behind the equivalence. As such, the author aurgues, the notion of community is to ground a question of pure difference: is there a possibility of a community that is not connected by what is the same?